PEMBENTUKAN DAN PENGUKURAN KINERJA PORTOFOLIO EFISIEN DENGAN METODE CONSTANT CORRELATION MODEL MENGGUNAKAN GUI MATLAB (Studi Kasus: Kelompok Saham pada Indeks JII, LQ45, dan INFOBANK15) - Muhammad Zidan Eka Atmaja; Alan Prahutama; Dwi Ispriyanti (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2021)
Investment is an important part of financial management that is widely known by the public. One example of an investment is a stock, stock is favored by investors because many of companies issue stock investment. investors goal from investment are to get funds that have been invested. Besides advantage, investors also have to face risks that can befall on him. Risk in investment can be minimized by diversification, for example by forming a portfolio. A good portfolio is an efficient portfolio, which is a portfolio that has a high rate of return with minimal risk. One of the way to to form an efficient portfolio is the Constant Correlation Model (CCM) method. The CCM method focuses on Excess return to Standard Deviation (ERS) and correlation between paired stocks. And to measure the portfolio formed can be measured by the Sharpe Ratio. GUI MATLAB program was formed to make it easier to find portfolio from the CCM method. This research uses stock data on the stock index JII, LQ45, and INFOBANK15 with interest rate of SBI period 2 October 2017-30 December 2019. Based on the results and discussion with manual calculations and GUI MATLAB, it can be concluded that percentage of weight, expected return, risk, and Sharpe index produce the same numbers. Keywords: Stock, Efficient Portfolio, Constant Correlation Model, Sharpe Ratio